Ativação de caspase-1 durante a infecção por Plasmodium: avaliação dos componentes envolvidos e implicações na patogênese da Malária. - Marco Antônio Ataíde Silva (2011)
Malaria is a major cause of death worldwide infecting around half-billion people annualy. Years of studies on malaria pathogenesis has funneled into consent: malaria is a highly pro-inflammatory disease where clinical manifestations are directly correlated with the induction of high levels of pro-inflammatory mediators. Here we demonstrated a pre-formed ASC dimers and active caspase-1 in monocytes from P.vivax infected patients. Furthermore was observed immediate release of IL-1β by peripheral blood mononuclear cells stimulated with LPS. Additionally we show a new feature of malaria pathogenesis with deleterious consequences even for the non-lethal murine model, Plasmodium chabaudi. We report that caspase 1 is persistently active in macrophages and dendritic cells during acute murine malaria, being this phenomenon NLRP3 and NLRP12 inflammasome-dependent. Usually, P.chabaudi infection resolves at fourth week, but challenging of acute infected mice with low doses of LPS resulted in alarming levels of IL-1β and TNFα, culminating in septic shock-like sydrome and ultimately death. Susceptibility of mice to low LPS doses was associated with a high background of caspase 1 activation and release of IL-1β. We have shown that MyD88, ASC, IFN-γ and TNFR1 signaling controls these events. Together, our results show that the inflammasomes platform is fully assembled and ready to generate high IL-1β levels if an inducer of pro-IL1β, such as TLR agonists, is present during malaria infection.